Menakar Demokrasi Pasca Pemilu: Refleksi Kritis Terhadap Partisipasi, Transparansi, Dan Konsolidasi Demokrasi Di Indonesia - Rikardo, Yanuar (Jurnal Dehasen Untuk Negeri, 2023)
This community service activity aims to critically evaluate the post-election democratic process in Indonesia, particularly in terms of public participation, electoral transparency, and the challenges of democratic consolidation. Conducted at RRI Bengkulu, the program featured an interactive dialogue involving academics, media professionals, students, and the general public. The findings indicate that while voter turnout was relatively high, major challenges persist—especially in reinforcing the role of the opposition, empowering civil society, and resisting oligarchic control in politics. Transactional politics and misinformation campaigns remain significant obstacles to a healthy democracy. Utilizing live broadcasts and social media platforms, this initiative successfully reached a broad audience and fostered collective political awareness. Post-event evaluations revealed improved public understanding of the importance of civic oversight and the need for continuous political education. This program serves as a model for community engagement that not only responds to contemporary issues but also proactively shapes responsible, critically minded democratic citizens.